الكتب المقدسة عند اليهود - التلمود انموذجا - - رحاب عماري; د/ عبدالوهاب كيدار (جامعة عمار ثليجي الاغواط, 2024)
المـــــــــــــــلخص يعد الدين مهد الحضارات الإنسانية منذ القدم، بل إن أغلب البشر على مر العصور تعتنق أدياناً و تتعصب لها ، ولاشك أن الدين من أكبر العوامل لتحديد الهوية الخاصة لكل مجتمع و تميزه عن غيره من المجتمعات من خلال عباداتهم و معتقداتهم الدينية وهي التي تحدد ممارسات و سلوكيات الإنسان من عادات وتقاليد وأحكام وقوانين... ومنها إحتلت دراسة الدين موقعاً بارزاً في فهم الحضارات القديمة بغض النظر عن طبيعة هذا الدين سواء كان دينٌ وضعي من صنع البشر أو ديناً سماوياً منضبط في أركانه وأهدافه وغاياته ويتمثل في الأديان السماوية الثلاثة . Abstract Religion has been considered the cradle of human civilizations since ancient times. In fact, most people throughout the ages have embraced religions and become fanatical about them. There is no doubt that religion is one of the biggest factors in determining the special identity of each society and distinguishing it from other societies through its religious worship and beliefs that determine human practices and behavior, including customs, traditions, rules and customs. Laws... including the study of religion occupied a place in the understanding of ancient civilizations, regardless of the nature of this religion, whether it was a positive religion or a divine religion, disciplined in its goals and objectives, and represented by the three heavenly religions